Mathematics Education Game Using the Finite State Machine Method to Implement Virtual Reality in Game Platformer - ,; , (Inform : Jurnal Ilmiah Bidang Teknologi Informasi dan Komunikasi, 2020)
Rapid technological developments have changed the patterns and systems that existed before. One of them is a Gim that has collaborated with the world of Education, the Gim is called an educational Gim. There are advantages in building an educational Gim that is visualization of real problems and increasing interest in learning. Mathematics is one of the subjects that is considered difficult for students. This is due to a lack of understanding of students in mastering the material given. In grade 5 elementary school students, desperately need rapid understanding because the class students receive more material and lessons from the previous class. The Finite State Machine method that was applied to the Gim "The Story of Rino’s Life" with additional multimedia and storyline, the Gim became more interesting and fun to play. The results of this study indicate that this Gim has fulfilled the needs of players, namely as a learning medium that makes it easier for students in grade 5 to understand mathematical material and also provides motivation to always learn mathematics.